Effect of rice-duck co-cultivation on the trend of changes in growth indices, photosynthesis and irrigation and precipitation water productivity in different cultivation systems - Kamran Mansour Ghanaei-Pashaki; Golam Reza Mohsen abadi; Mohammad Hassan Bigluei; Mohammad Bagher Farhangi; Ali Mokhtassi-Bidgoli (Journal of Agricultural Science and Sustainable Production, 2022)
Background and Objective: This study was conducted to investigate the combined use of duck in different rice cultivation systems on growth indices, photosynthesis and water productivity of fields.Materials and Methods: The experiment was carried out as a split plot factorial experiment based on randomized complete block design with three replications in Research Farm, Faculty of Agricultural Sciences, University of Guilan, in 2017 and 2018 years. Treatments included of three levels of cultivation system; Conventional Cultivation (CC), Improved Cultivation (IC) and SRI (System of Rice Intensification) as the main factor and combined of two levels of duck (control and 750 duck per hectare) and three levels of weed control (control, once and twice weeding) factorials as a sub-factor.Results: The results showed that the beginning of the growing period, all experiment treatments showed a significant difference in terms of leaf area index and with increasing the length of the growing period; the increase in leaf area index was greater in terms of combine treatments of 750 ducks per hectare and SRI. At the beginning of growth, CGR in SRI system was slower than the others and in the middle to late growth period, CGR rate values were in SRI>IC>CC. In un-use duck conditions, Conclusion: In general, the combined application of rice-duck in different cultivation systems can be considered suitable for improving the quantitative yield and growth and physiological indicators of rice to achieve sustainable agricultural goals and increase farmers' income per unit area in the plain areas of Guilan.